Development of Malignant Melanoma of the Orbit in Previous Radiation Field. (November 2015) - Ahmed, Shamima; McDonald, Nicholas; Lowder, Lindsey; Mahoney, Bruce
Abstract : Abstract: We present a case of a 40-year-old woman with a history of retinoblastoma in the left eye treated with enucleation and radiation therapy as an infant who recently developed worsening pain and exophthalmos in her right eye. Multimodality imaging demonstrated an enhancing, FDG-avid mass in the medial right orbit with associated bone destruction and extension into the ethmoid sinus. Pathologic analysis after excision showed a highly undifferentiated tumor consistent with melanoma. Although development of malignant melanoma in an irradiated field is rare, it should be considered in the differential, especially in childhood cancer survivors at increased risk of second malignant neoplasms.